Turkish delight for some, cold turkey for others?: The effects of the EU-Turkey Customs Union - Antonis Adam; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2005)
Following Turkey's application for EU membership in 1987, a Customs Union (CU) between Turkey and the EU, mainly covering trade in manufacturing goods and processed agricultural products, came into effect in 1995. In addition to a large agricultural sector, Turkey also specializes in the production and exportation of relatively low-price, low-quality varieties of manufactured products. We use a theoretical framework in order to demonstrate that these features of the Turkish economy imply asymmetric changes in the trade volumes of the incumbent countries of the EU as a result of the EU-Turkey CU. By examining disaggregated trade data we find that the technologically sophisticated EU countries (e.g., mainly the Northern European countries) are also least similar to Turkey in terms of their export structure, whereas the degree of export similarity between the less technologically sophisticated EU members and Turkey is high. Our econometric results indicate that, in contrast to the “Northern” group's exports to other EU15 countries (which have remained intact), the Southern countries's exports to the other EU15 countries have declined as a result of the EU-Turkey CU. Moreover, the extra penetration of the Turkish market by EU countries has not been more favourable to the Southern group. These findings also imply that technologically sophisticated countries may see no significant further benefits from Turkey's full accession to the EU (whereas the migration and political influence related costs for these countries may be large).
Keywords: F15; F13; 330; European Union; Turkey; customs union; exports; gravity; differentiated products; Zollunion; Wirtschaftspolitische Wirkungsanalyse; Außenhandelseffekt; Internationale Arbeitsteilung; Außenhandelsstruktur; Gravitationsmodell; Schätzung; Theorie; Türkei; EU-Staaten; Nordeuropa; Südeuropa